2020
DOI: 10.3390/w12072067
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Taxonomic Composition as a Biological Indicator of the Ecological Health and Status of a River Basin under Agricultural Influence

Abstract: The Lalin River Basin (LLRB) is a major drainage basin in northeastern China, that has been significantly influenced by agricultural activities. This study focused on exploring diatom taxonomic composition linked to environmental factors at the taxonomic levels of genus and species during ice-covered periods. Nine sampling stations were divided into three groups based on trophic state index (TSI). hierarchical cluster analysis (HCA) and redundancy analysis (RDA) were performed to identify diatom distribution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Recently, homogenization of diatom communities has also been observed in response to hydrological alterations and urbanization in Mediterranean rivers which also led to significant species loss at both local and regional scales (Falasco et al, 2021a) and a reduced role of diatoms in the total benthic chlorophyll-a (Piano et al, 2016). Moreover, the present study confirmed the high trophic value of some species, mainly collected in the R-C macrotype, such as N. gregaria (Hicks and Taylor, 2019;Hausmann et al, 2016;Szczepocka et al, 2016), Nitzschia palea (Licursi et al, 2016;Szczepocka et al, 2016;Yang et al, 2015), Gomphonema parvulum (Lu et al, 2020;Szczepocka et al, 2016) and C. euglypta (Trábert et al, 2020). S. nigri was confirmed as one of the most tolerant diatom species (see Hausmann et al, 2016 as Eolimna minima;Yang et al, 2015).…”
Section: Diatom Communities and Water Quality In The Two Macrotypessupporting
confidence: 82%
“…Recently, homogenization of diatom communities has also been observed in response to hydrological alterations and urbanization in Mediterranean rivers which also led to significant species loss at both local and regional scales (Falasco et al, 2021a) and a reduced role of diatoms in the total benthic chlorophyll-a (Piano et al, 2016). Moreover, the present study confirmed the high trophic value of some species, mainly collected in the R-C macrotype, such as N. gregaria (Hicks and Taylor, 2019;Hausmann et al, 2016;Szczepocka et al, 2016), Nitzschia palea (Licursi et al, 2016;Szczepocka et al, 2016;Yang et al, 2015), Gomphonema parvulum (Lu et al, 2020;Szczepocka et al, 2016) and C. euglypta (Trábert et al, 2020). S. nigri was confirmed as one of the most tolerant diatom species (see Hausmann et al, 2016 as Eolimna minima;Yang et al, 2015).…”
Section: Diatom Communities and Water Quality In The Two Macrotypessupporting
confidence: 82%
“…The dominating species in epilithon, Achnanthidium minutissimum, is well-known as a species adapted to a high velocity environment [61], whereas the species that were found in high abundances in the epiphyton community are often found in a high nutrient environment under agricultural influence (e.g., Gomphonema spp. and Encyonema sp., Table S3) [62]. Therefore, differences in species composition of the epiphyton and epilithon support that the epilithon is more dependent on the water-nutrient concentration and hydraulic disturbances, validating the H2 and H3 hypotheses.…”
Section: Discussionsupporting
confidence: 63%
“…3− concentration compared to Lyngbygård [62]. Thus, although the two study streams showed similar land use and catchment size, local differences driven by light, DOC and PO 4 3− were important to site-specific biofilm structure.…”
Section: Discussionmentioning
confidence: 79%
“…exigua, N. menisculus, and N. viridula are distributed in the negative position of axis 2. In terms of ecological affinity, A. exigua is more common in eutrophic polluted waters [88], and N. menisculus is commonly found in freshwaters such as swamps, lakes, and rivers and endures organic pollution with high tolerance to inorganic eutrophication [89], while N. viridula exists in waters with high nitrogen and phosphorus [78] and occurs in eutrophic rivers in China [90]. They all prefer to live in waters with high eutrophication.…”
Section: Pca Results and Ecological Affinity Of Diatomsmentioning
confidence: 99%